Sufi Spiritual Values in the Qur'an: A Thematic Exploration of Tazkiyah al-Nafs : - Ahmad Ali Syauqi Fathan; Fathur Rohim; Zidan Rosyadi Fathan (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This article explores the Qur'anic concept of tazkiyah al-nafs (purification of the soul) through the lens of Sufi values, emphasizing key spiritual principles such as muraqabah (self-awareness), jihad al-nafs (striving against the ego), ikhlas (sincerity), taqwa (piety), and sabr (patience). By employing a thematic analysis of selected Qur'anic verses, the study examines how these values serve as foundational components of Sufi education, with a particular focus on their ethical and moral dimensions. The findings highlight that these values, derived directly from the Qur'an, are essential for the cultivation of a spiritually and ethically aware individual.The study further argues that integrating these Sufi principles into contemporary Islamic educational frameworks can play a crucial role in addressing the growing moral and spiritual crises in modern education systems. This integration could help foster not only intellectual growth but also the development of a balanced and virtuous character, aligning education with Islamic ethical teachings. In conclusion, the study presents tazkiyah al-nafs as a transformative model for ethical and spiritual education, offering practical implications for revitalizing Islamic education in the modern world.